1994
DOI: 10.3109/00365549409011780
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas maltophilia Bacteremia in Immunocompromised Hematological Patients

Abstract: Epidemiological, microbiological and clinical characteristics of 14 episodes of Xanthomonas maltophilia bacteremia in 12 seriously immunocompromised hematological patients, admitted to Rigshospitalet in Copenhagen over the 3-year period 1989-91, were evaluated. The results were compared with a randomly selected control group of 25 patients with Escherichia coli bacteremia. Hospital acquired bacteremia was more common among the patients with X. maltophilia bacteremia (p < 0.01). Treatment with broad-spectrum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 24 publications
1
58
1
4
Order By: Relevance
“…The presence of an indwelling CVC has been previously reported for 78% -86% of patients [23] [24] [35] [36]. This range is lower than the proportion in our figure which was 93.5%.…”
Section: Discussioncontrasting
confidence: 78%
“…The presence of an indwelling CVC has been previously reported for 78% -86% of patients [23] [24] [35] [36]. This range is lower than the proportion in our figure which was 93.5%.…”
Section: Discussioncontrasting
confidence: 78%
“…Recognized risk factors for S. maltophilia bacteremia in oncology patients have included severe and prolonged neutropenia, intravascular devices, prolonged hospital stay, aggressive chemotherapy treatment, and increased antibiotic pressure. 2,[6][7][8]23,24 Severe mucositis was recently identified as a significant risk factor for S. maltophilia bacteremia in the investigation of an outbreak among patients receiving bone marrow transplants. 8 Our study confirmed the association of severe mucositis with S. maltophilia bacteremia in oncology patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Although it is usually considered a colonizer and is rarely responsible for community-acquired infections, 5 its role as a pathogen has been increasingly recognized among immunocompromised patients, especially patients with malignancies. 2,[6][7][8] S. maltophilia accounted for 0.6% to 0.9% of all bloodstream infections reported from the United States, Canada, and Latin America from 1997 through 1999. 9,10 Septicemia due to this organism occurs rarely, although several nosocomial outbreaks have been reported.…”
Section: Stenotrophomonas Maltophilia Formerly Known Asmentioning
confidence: 99%
See 2 more Smart Citations